Transformational Leadership in Optimizing the Role of Learning Communities at SDN 007 Bangkinang and SDN 006 Langgini - Deni Arisanty; Meilina Bustari (FKIP - Universitas Riau, 2026)
This study aims to describe and analyze the inhibiting factors and strategies of school principals in implementing transformational leadership to optimize the role of learning communities at SDN 007 Bangkinang and SDN 006 Langgini, as well as their contributions to improving learning quality. A qualitative approach with a phenomenological design was employed. Data were collected through in-depth interviews with principals, teachers, and heads of learning communities, supported by documentation. Data analysis involved data condensation, data display, and inductive conclusion drawing. The findings indicate that at SDN 007 Bangkinang, major obstacles include high administrative workload, schedule imbalances, limited facilities, and low teacher motivation. At SDN 006 Langgini, obstacles mainly involve low teacher motivation, weak collective work culture, limited facilities, and poor coordination. To address these challenges, the principal of SDN 007 Bangkinang applies flexible scheduling, peer mentoring for administrative tasks, collaborative networking to support facilities, and transparent communication with parents. Meanwhile, the principal of SDN 006 Langgini fosters a psychologically safe climate for sharing, provides time flexibility, encourages needs-based mentoring, utilizes simple digital platforms, and builds partnerships with school committees. These strategies reflect transformational leadership practices that strengthen learning communities and enhance learning quality.